Ploidy-Dependent Effects of Light Stress on the Mode of Reproduction in the Ranunculus auricomus Complex (Ranunculaceae) - Ulum, Fuad Bahrul; Costa Castro, Camila; Hörandl, Elvira (Frontiers in Plant Science, 2020)
Polyploidy in angiosperms is an influential factor to trigger apomixis, the reproduction of asexual seeds. Apomixis is usually facultative, which means that both sexual and apomictic seeds can be formed by the same plant. Environmental abiotic stress, e.g. light stress, can change the frequency of apomixis. Previous work suggested effects of stress treatments on meiosis and megasporogenesis. We hypothesized that polyploidy would alter the stress response and hence reproductive phenotypes of different cytotypes. The main aims of this research were to explore with prolonged photoperiods, whether polyploidy alters proportions of sexual ovule and sexual seed formation under light stress conditions. We used three facultative apomictic, pseudogamous cytotypes of the Ranunculus auricomus complex (diploid, tetraploid, and hexaploid). Stress treatments were applied by extended light periods (16.5 h) and control (10 h) in climate growth chambers. Proportions of apomeiotic vs. meiotic development in the ovule were evaluated with clearing methods, and mode of seed formation was examined by single seed ﬂow cytometric seed screening (ssFCSS). We further studied pollen stainability to understand effects of pollen quality on seed formation. Results revealed that under extended photoperiod, all cytotypes produced significantly more sexual ovules than in the control, with strongest effects on diploids. The stress treatment affected neither the frequency of seed set nor the proportion of sexual seeds nor pollen quality. Successful seed formation appears to be dependent on balanced maternal: paternal genome contributions. Diploid cytotypes had mostly sexual seed formation, while polyploid cytotypes formed predominantly apomictic seeds. Pollen quality was in hexaploids better than in diploid and tetraploids. These findings confirm our hypothesis that megasporogenesis is triggered by light stress treatments. Comparisons of cytotypes support the hypothesis that ovule development in polyploid plants is less sensitive to prolonged photoperiods and responds to a lesser extent with sexual ovule formation. Polyploids may better buffer environmental stress, which releases the potential for aposporous ovule development from somatic cells, and may facilitate the establishment of apomictic seed formation.